Penerapan RAPID Application Development untuk Pengembangan Sistem Informasi Posyandu di Padukuhan Mertosan Wetan - Yumarlin MZ; Jemmy Edwin B; Putri Nawang Sari (Applied Information Technology and Computer Science (AICOMS), 2026)
Posyandu plays an important role in monitoring the health and growth of toddlers; however, the quality of its services in Pedukuhan Mertosanan Wetan still needs improvement. Posyandu activities carried out by midwives, health workers, and cadres still rely on manual recording using logbooks and Excel spreadsheets, resulting in various challenges such as data entry errors, inefficient data processing, and inaccurate or untimely reporting. These conditions hinder the effectiveness of Posyandu programs and highlight the need for a technological solution. This study aimed to design and develop a web-based Posyandu information system using the Rapid Application Development (RAD) method, which was selected due to its fast and effective development cycle. System feasibility was evaluated using the TELOS method (Technical, Economic, Operational, Legal, and Schedule) through questionnaires distributed to ten Posyandu cadres. The evaluation results showed a very good level of feasibility, with an overall score of 7.94, indicating that the system is easy to use, meets feasibility criteria, and is suitable for implementation at the Posyandu in Pedukuhan Mertosanan Wetan.